2016
DOI: 10.1590/s0080-623420160000700007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating pharmaceutical waste disposal in pediatric units

Abstract: Objective:To verify the disposal of pharmaceutical waste performed in pediatric units. Method: A descriptive and observational study conducted in a university hospital. The convenience sample consisted of pharmaceuticals discarded during the study period. Handling and disposal during preparation and administration were observed. Data collection took place at pre-established times and was performed using a pre-validated instrument. Results: 356 drugs disposals were identified (35.1% in the clinic, 31.8% in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
(14 reference statements)
0
5
0
Order By: Relevance
“…After removing duplicates, 2313 studies were screened by title and abstract, yielding 699 articles for full-text review. From that set, ultimately 156 studies were eligible for inclusion in the qualitative synthesis (Supplemental Table S1) (Abd El-Salam, 2010; Abu Qdais et al, 2007; Alam et al, 2008; Al-Dhawailie, 2011; Alhumoud and Alhumoud, 2007; Ali, 2019; Ali and Geng, 2018; Ali et al, 2016a, 2016b; Al-Khatib et al, 2019; Almeida et al, 2016; Almuneef and Memish, 2003; Altin et al, 2003; Alves et al, 2014; Al-Zahrani et al, 2000; Andrade et al, 2014; Asante et al, 2014; Askarian et al, 2010; Awad et al, 2004; Azage and Kumie, 2010; Babu et al, 2019; Barbario et al, 2021; Bassey et al, 2006; Bazrafshan and Mostafapoor, 2011; Bdour et al, 2007; Caniato et al, 2016; Carr et al, 2019; Chiang et al, 2006; Chitnis et al, 2005; Chua et al, 2021; Conrardy et al, 2010; Debere et al, 2013; Debita et al, 2017; Dehghani et al, 2008, 2019; Denny et al, 2019; de Sa et al, 2016; De Sousa et al, 2014; Dewi et al, 2019; Dias et al, 2017; Diehl et al,1992; Dietrich et al, 2004; Doiphode et al, 2016; Dumitrescu et al, 1998; Farmer et al, 1997; Farzadkiaet al, 2009; Fasola et al, 2008; Ferdowsi et al, 2012; …”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, 2313 studies were screened by title and abstract, yielding 699 articles for full-text review. From that set, ultimately 156 studies were eligible for inclusion in the qualitative synthesis (Supplemental Table S1) (Abd El-Salam, 2010; Abu Qdais et al, 2007; Alam et al, 2008; Al-Dhawailie, 2011; Alhumoud and Alhumoud, 2007; Ali, 2019; Ali and Geng, 2018; Ali et al, 2016a, 2016b; Al-Khatib et al, 2019; Almeida et al, 2016; Almuneef and Memish, 2003; Altin et al, 2003; Alves et al, 2014; Al-Zahrani et al, 2000; Andrade et al, 2014; Asante et al, 2014; Askarian et al, 2010; Awad et al, 2004; Azage and Kumie, 2010; Babu et al, 2019; Barbario et al, 2021; Bassey et al, 2006; Bazrafshan and Mostafapoor, 2011; Bdour et al, 2007; Caniato et al, 2016; Carr et al, 2019; Chiang et al, 2006; Chitnis et al, 2005; Chua et al, 2021; Conrardy et al, 2010; Debere et al, 2013; Debita et al, 2017; Dehghani et al, 2008, 2019; Denny et al, 2019; de Sa et al, 2016; De Sousa et al, 2014; Dewi et al, 2019; Dias et al, 2017; Diehl et al,1992; Dietrich et al, 2004; Doiphode et al, 2016; Dumitrescu et al, 1998; Farmer et al, 1997; Farzadkiaet al, 2009; Fasola et al, 2008; Ferdowsi et al, 2012; …”
Section: Resultsmentioning
confidence: 99%
“…The disposal of medicines from the antiulcer class in household waste represented 4.65% (Figure 2A). Almeida et al (2016) found that the most discarded pharmaceuticals in pediatric units were from the antimicrobial (22.7%), electrolyte (14.8%), analgesic (14.6%), diuretic (9.5%), and antiulcer (6.7%) classes.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-infective medicines and cardiovascular medicines wastage was 18.9% and 8.9% in tertiary Hospitals in Dar Es Salaam [ 10 ] and Sweileh et al study in Palestinian hospital showed that alimentary, musculoskeletal, and anti-infective agents were the most common categories [ 9 ]. The University hospital pediatric units of Brazil showed that 22.7% antimicrobials, 14.8% electrolytes, 14.6% analgesics/pain killers, 9.5% diuretics, and 6.7% antiulcer agents were wasted [ 43 ]. This might be attributed to health facilities in developing countries like Ethiopia were more prone to infectious disease as they demand more anti-infective.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, normal waste bins used for over 75% disposed of pharmaceuticals in selected hospitals of Ghana [ 50 ]. In the University hospital of Brazil, sharps’ disposable box with a yellow bag, sink drain, sharps box with orange bag, and infectious waste/bin with a white bag was used [ 43 ]. When planning storage of waste, the characteristics of the specific chemicals to be stored and disposed of must be considered [ 17 ] and all waste-bag seals should be in place and intact until they are transported to disposal sites [ 51 ].…”
Section: Discussionmentioning
confidence: 99%